Pengaruh Jarak Tanam dan Aplikasi Kotoran Kelinci terhadap Pertumbuhan dan Hasil Tanaman Kacang Hijau (Vigna radiata L.) - Aldianto mau awang; Ida Bagus Komang Mahardika; Anak Agung Ngurah Mayun Wirajaya (Fakultas Pertanian, Universitas Warmadewa, 2023)
Green beans have advantages over other food crops in terms of agronomy and economy, such as: (1) shorter-lived between (55-65 days) can be harvested, (2) more drought-resistant with relatively small water requirements for green bean growth, namely 700-900 mm / year. In rainfalls that are lower than that, it can still grow because it is deeply rooted, (3) it can be planted on less fertile land and fertilize the soil because it is symbiose with rhizobium and produces as much biomass (11-12 t/h), (4) easy cultivation methods are sufficiently minimal tillage and seeds are sown, (5) pest attacks are less diseased and (6) the selling price is high and stable. The purpose of the study was to determine the effect of planting distance and application of rabbit manure on the growth and yield of green bean plants (Vigna radiata L). The experimental design used was with a randomized design of the group and the analysis of the F test (analysis of variance) on the. This research was carried out in Subak Rapuan, Mas Village, Ubud District, Gianyar Regency with an altitude of 400 meters above sea level. The implementation of the study starts from March - June 2022. The highest fresh weight of seeds at the spacing treatment (J3) can be caused by wide planting distances and optimal fertilizer application. The wider planting distance provides space for access to sunlight, air temperature, and air humidity that can contribute to the growth and development of plants. The wider planting distance will reduce the competition higher so that with the J3 planting distance, it reduces the occurrence of nutrient competition so that the nutrients given through K3 fertilization will be used properly by plants. This shows that a dose of rabbit manure of 15 tons/ha-1 has the best effect on the growth of green beans so that it gives high yields compared to doses of 5 tons/ha-1 and 10 tons/ha-1. The fresh weight of seeds per plant is strongly supported by the presence of correlations in the number of pods (r = 0.889**) the length of the pods (r = 0.828*) and the number of seeds (r = 0.921**).